OS 31-01 BLOOD PRESSURE, INITIAL ORTHOSTATIC HYPOTENSION, GLYCERYL TRINITRATE AND THE GLU504LYS POLYMORPHISM OF ALDEHYDE DEHYROGENASE-2. (September 2016) - Harrap, Stephen; Lamantia, Angela; Ziogas, James; Bourke, Jane
Abstract : Objective: Glyceryl trinitrate (GTN) is used to treat angina and lower blood pressure. The enzyme mitochondrial aldehyde dehydrogenase-2 (ALDH2) can activate GTN. The polymorphism (Gly504Lys) in the gene encoding ALDH2 is associated with significantly reduced enzyme activity and potentially diminished responses to GTN. Design and Method: Systolic blood pressure (SBP) was measured continuously (Finometer Midi) during 2 orthostatic challenges in 493 healthy young adults (mean age 22 y), 390 of whom took 300 μg GTN sublingually 5 min prior to the second challenge and 103 subjects of whom were untreated. We recorded the average SBP for 30 s after 5 minutes lying, the nadir in SBP within 30 s of standing and the average SBP for 30 s after 2 minutes standing. The ALDH2 polymorphism was measured by the SNP rs671 (allele A = Lys, allele G = Gly). A dominant model (GG v AG/AA) was use to compare SBP with adjustments for age, sex and weight. Results: During the control challenge in the GTN group, the mean lying SBP was 117 mmHg (SD 15.8), 73 mmHg (20.4) on initial standing and 109 mmHg (16.9) after 2 minutes standing. After GTN, SBP was significantly (all P < 0.0001) lower than control lying [114 mmHg (15.9)], on standing [60 mmHg (19.3)] and after 2 minutes standing [103 mmHg (16.9)]. In the 103 untreated subjects there were no significant differences between the SBP between challenges. None of the SBP responses after GTN differed between the 2 ALDH2 genotype groups. Conclusions: In healthy young adults acute GTN causes a major exaggeration of the initial orthostatic hypotension within 30 s of standing. The hypotensive actions of GTN were not associated with the Gly504Lys polymorphism. These findings suggest that factors other than ALDH2 activity explain the blood pressure effects of acute exposure to GTN.